Selbstentfaltung – Das Formen der Person und die Ausdifferenzierung des Subjektiven: Soziologische Übersetzungen II - Renn, Joachim (transcript, 2016)
The individual (as the name for that which is dispersed in the environment of the problem of the subject) is socially determined in its realization: the individual is formed (socialized, disciplined, subjectivized) – and must also, either parallel to or against this, form itself, self-direct its own individuation and authentication. Joachim Renn's study shows how `self-realization' as `differentiation' can be the basic figure of a pragmatic sociology of the `subjective' in society. The central theoretical problem then becomes the relationship between general forms of the genesis of subjective self-relations and the socio-historical variation of interlocking and diffusion of subject formats and subjective `self-relations'.